Organizational changes in Canada's sport system: Toward an Athlete-Centred approach - Thibault, L.; Babiak, K. (European Sport Management Quarterly, 2005)
Prompted by an examination of the sport system, a reorientation of priorities and actions around high performance sport has occurred in Canada. One of the important changes has been a shift away from the administrative aspects of sport delivery to a focus on the development of high performance athletes. This shift has meant that more resources are now invested directly in high performance athletes rather than in the administration of sport organizations. The purpose of this paper was to explore the reorientation in priorities, from the bureaucracy of sport to the athletes and their development. Using Pettigrew's contextualist approach, we examined the content, context, and process of changes that led to the introduction of athlete-centred initiatives in Canada's sport system. Evidence of the change included increased representation of athletes on decision-making committees of sport federations, increased athlete funding, the creation of training centres, and a forum for athletes to resolve disputes with coaches and sport federations. The change to a more athlete-centred system was the result of pressures originating from the external and internal environments. Key individuals also played an important role in the athlete-centred change. The application of Pettigrew's approach allowed us to discuss the nature of the changes that took place and to better understand the complexity of the change process in light of pressures originating from the context. This paper allowed us to reflect on the reorientation in Canadian sport from a focus on the structural and bureaucratic development of the system to an athlete-centred approach. We also discussed system-wide changes occurring in Canadian sport and uncovered the factors that led to greater athlete-centred programs and services.